Luminescent pyrrole-based phosphaphenalene gold complexes: versatile anticancer tools with wide applicability - Fermi, Valentina; Regulska, Elzbieta; Wolfram, Anna; Weßling, Patrik; Rominger, Frank; Herold-Mende, Christel; Romero-Nieto, Carlos (Chemistry - a European journal, 2022)
Invited for the cover of this issue are the groups of Christel Herold-Mende and Carlos Romero-Nieto at the Universities of Heidelberg and Castilla-La Mancha. The image depicts the use of phosphaphenalene gold(I) complexes for the treatment of brain cancer. Read the full text of the article at 10.1002/chem.202104535.